Quality of Life in Chronic Diseases - Hamza Khalifa Ibrahim; Hamza A. khalfallah; Zahrah Meelad Eisay; ADMIR JANCE; Aejeeliyah Yousuf (Green Publisher Indonesia, 2022)
Over the past few decades, there has been a increasing prevalence of chronic diseases, live with a large number of people chronic diseases that may adversely affect them quality of life. The goal of the current work is to To investigate quality of life, particularly health-related quality of life (HRQoL) in patients with chronic diseases. HRQOL is a multidimensional structure It consists of at least three large domains − physical, mental and social functioning − affected by disease and/or treat. HRQoL usually starts with chronically ill and often impaired most. In addition, the following factors Also correlated with good and bad HRQoL Discussed as HRQoL assessment. That Estimating the relative impact of chronic diseases Necessary for HRQoL disease Better plan and allocate healthcare Resources to Improve HRQoLOver the past few decades, there has been a increasing prevalence of chronic diseases, live with a large number of people chronic diseases that may adversely affect them quality of life. The goal of the current work is to To investigate quality of life, particularly health-related quality of life (HRQoL) in patients with chronic diseases. HRQOL is a multidimensional structure It consists of at least three large domains − physical, mental and social functioning − affected by disease and/or treat. HRQoL usually starts with chronically ill and often impaired most. In addition, the following factors Also correlated with good and bad HRQoL Discussed as HRQoL assessment. That Estimating the relative impact of chronic diseases Necessary for HRQoL disease Better plan and allocate healthcare Resources to Improve HRQoL